Manajemen Evaluasi Kinerja: Dampak Kepemimpinan di The Jungle Bogor - Adie Nugraha Natanegara; Sri Sundari; Marisi Pakpahan (Journal of Management and Social Sciences, 2024)
This journal aims to analyze organizational performance evaluation by focusing on the impact of leadership at The Jungle Waterpark Bogor. The research involves data collection through feedback from various levels and functions within the organization, encompassing the perspectives of employees from various departments. Performance evaluation is conducted by considering factors such as employee well-being, recognition of rights, and interactions with leadership. The results of this study provide an in-depth understanding of how leadership influences organizational dynamics and employee performance in the entertainment industry.